Kinerja Perusahaan sebagai Pemediasi Pengaruh Penerapan Employee Stock Option Plan (ESOP) pada Nilai Perusahaan - Ayu Wisma Dewi, Ni; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 30 No 4 (2020), 2020)
Limited liability company (Ltd) based on a contract cooperative relationship which is the basis of agency theory with the risk of conflict. The solution to minimize is the employee stock ownership program with the Employee Stock Option Plan (ESOP) strategy. The purpose of this study is to obtain empirical evidence of the relationship of stock options granted’s number to the firm value through firm performance. This research was conducted at companies listed in the BEI and conducted ESOP grants in 2014-2018. Samples obtained using purposive sampling were 48 observations. Data analysis technique used is path analysis. The results showed that the number of stock options granted had a positive effect on firm performance, firm performance had a positive effect on firm value, the number of shares options granted had a positive effect on firm value, and firm performance mediated the relationship between the number of shares options granted and firm value. Keywords: Employee Stock Option Plan; Firm Performance; Firm Value.